Parent Parenting Patterns For Pre-School Children In Sarimarrihit Village, Sianjur Mula-Mula In 2021 - Andi Novel Limbong (Sean Institute, 2022)
Background: Parenting is a process that is given to improve and support the physical, emotional, social, financial, and intellectual development of a child from infancy to adulthood. Parents are the first picture for children to learn many things, both academically and in life in general. The purpose of this study was to identify parenting patterns in Sarimarrihit Village, Sianjur at first.Methods: The research method used is descriptive. Results: The research shows that all parents respondents in Sarimarrihit Village, Sianjur initially chose democratic parenting with demographic data aged 31-40 years as many as 8 respondents (40%) preferred democratic parenting. The majority of education levels are SMA and D3 as many as 6 respondents, the majority of parents work as farmers as many as 12 respondents. It is hoped that parents will maintain good parenting patterns in raising children and modify parenting patterns.Discussion: It is expected that parents will continue to maintain good parenting patterns in raising children and modify parenting patterns. Conclusion The parenting pattern of pre-school children in Sarimarrihit Village, Sianjur initially used more democratic parenting as many as 20 respondents.